Evaluation of the role of the clinical Nurse Specialist in cancer care: an integrative literature review - Kerr, Helen; Donovan, Monica; McSorley, Oonagh (European journal of cancer care, 2021)
Introduction Although there is growing evidence the Clinical Nurse Specialist role makes a difference to patient care, the full value of this service may not be always appreciated with current models not meeting the needs of those with cancer. The primary aim of this integrative literature review was to evaluate outcomes associated with the role of the Clinical Nurse Specialist in cancer care. The secondary aim was to identify the components of the Clinical Nurse Specialist role in cancer care from the included papers in the literature review. Methods An integrative literature review using a systematic approach was adopted. Literature searches were undertaken in four databases and supplemented with a search in the grey literature and reference lists of included papers. Searches were limited to January 2009‐July 2019 and those written in the English language. Three reviewers independently completed the searches and reviewed the papers before reaching a consensus. Results Fourteen eligible research papers were identified. Evaluations were predominately positive with the role contributing to improving patient outcomes with regards psychological support, information provision, symptom management, service coordination and patient satisfaction. Conclusion The findings of this literature review firmly establish the Clinical Nurse Specialist as a valuable member of the multidisciplinary team in enhancing cancer care services.